A mechanistic study of the interactions between methane and nickel supported on doped ceria - Ouyang,M; Boldrin,P; Maher,R; Chen,X; Liu,X; Cohen,L; Brandon,N (Applied Catalysis B: Environmental, 2019)
A novel combined method using modified methane pulses and in-situ Raman spectroscopy together with mass spectrometry is applied to impregnated Ni/gadolinium-doped ceria (CGO). The partial oxidation of methane is deduced to proceed via a Mars-van-Krevelen type mechanism composed of initial methane decomposition together with carbon oxidation by oxygen from CGO. The critical role of the ceria surface and the bulk oxygen in the reaction is defined in detail. Oxygen is a necessary reactant in the reaction, as well as inhibiting carbon deposition. Oxygen spill-over is the driving force for the carbon oxidation and the ceria surface oxygen is resupplied by bulk oxygen after depletion. Bulk migration of oxygen to the surface is the rate-determining step. We also demonstrate that the ceria oxygen stoichiometry significantly affects the type of reaction and the rate of reaction between methane and Ni/CGO: The total oxidation of methane happens only when the oxygen stoichiometry is high while the oxygen spill-over rate decreases with decreasing oxygen stoichiometry, which reduces the rate of carbon elimination and results in reduction in the rate of methane oxidation. This work lays out a comprehensive evaluation methodology and provides important insights for future design of methane oxidation catalysts for solid oxide fuel cells, and more widely for methane reforming with different oxidants (steam, CO2, NO2 etc).